2021
DOI: 10.1111/cas.15067
|View full text |Cite
|
Sign up to set email alerts
|

Plasma extracellular vesicle microRNA‐491‐5p as diagnostic and prognostic marker for head and neck squamous cell carcinoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…A recent study found that increased plasma EVs miR-491-5p levels were associated with poor overall survival and disease-free survival in HNSCC patients. Plasma EVs miR-491-5p was able to distinguish HNSCC patients with sensitivity and specificity of 46.6% and 100%, respectively [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that increased plasma EVs miR-491-5p levels were associated with poor overall survival and disease-free survival in HNSCC patients. Plasma EVs miR-491-5p was able to distinguish HNSCC patients with sensitivity and specificity of 46.6% and 100%, respectively [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a model based on EV-miR-491-5p expression was developed as a prediction tool to discriminate between patients with HNSCC and healthy controls, showing a sensitivity and specificity of 46.6% and 100%, respectively. Furthermore, it was found that the dynamic change of miRNA-491-5p pre- vs. post-treatment was associated with the 1-year disease recurrence rate (80% sensitivity and 69.23% specificity), as well as disease free survival and overall survival (HR of 2.82 and 5.66, respectively) [ 123 ]. This finding might help identify HNSCC patients who are at high risk of tumor recurrence.…”
Section: Ev-mirnas In the Clinical Management Of Hnsccmentioning
confidence: 99%
“…Momen-Heravi and Bala [ 100 ] identified circulating EVs from plasma of OSCC patients enriched with miR-21, miR-27b, and miR-27a. Panvongsa et al [ 101 ] observed that four miRNAs in plasma-derived EVs (miR-27b-3p, miR-491-5p, miR-1910-5p, and miR-630) were significantly dysregulated in locally advanced HNSCC compared with healthy donors, being ΔmiR-491-5p associated with OS and DFS. Salivary exosomal miRNAs have been investigated in OSCC patients, being found significant increase in miR-24-3p, miR-512-3p, and miR-412-3p levels in patients compared to controls [ 102 , 103 ].…”
Section: Evsmentioning
confidence: 99%
“…Liquid biopsy is a promising investigation area in the oncology field, being successfully described in translational studies [ 11 , 36 , 55 , 82 , 101 ]. Besides being a minimally invasive procedure, the major clinical interest in liquid biopsy is that molecular alterations detected in circulating biomarkers may reflect the alterations found in tumor tissues, thus reducing the number of invasive biopsies to monitor the tumor process.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%